A two‐tiered structure device based on stereolithography for residual mandible repositioning in mandibular reconstruction with fibular flap. Issue 6 (21st April 2016) - Kadowaki, Miki; Kubo, Tateki; Fujikawa, Masakazu; Tashima, Hiroki; Nagayama, Hiromi; Ishihara, Osamu; Yamada, Ryuhei; Otake, Ippei; Hosokawa, Ko
Abstract : Objective: We invented a two‐tiered structure device based on stereolithography for residual mandible repositioning in mandibular reconstruction with fibular flap, and examined its usefulness. Patients and methods: A total of eight patients (six carcinomas and two osteomyelitis) who had undergone mandibular reconstruction with fibular flap were included. Mandibular defects according to Jewer's classification were L for five, LC for two, and H for one patient (range of bone defect size, 7.7‐13.3 cm). Based on a stereolithographic mandibular model, a two‐tiered structure device was made preoperatively with resin, and was applied during surgery to define the accurate position of residual mandible following segmental mandibulectomy. Postoperative aesthetic and functional outcomes, including dental status, diet, and speech were evaluated. Results: The device was applied without any problems during surgery. Follow‐up period ranged from eight to twenty‐two months. Good postoperative alignment of the grafts and occlusion were also achieved in all eight patients. Five patients were able to return to eating meals as they had pre‐surgery, and two patients required dental rehabilitation with dentures. As for speech, four patients scored ten points, three patients scored eight points, and one patient scored four points in Hirose's scoring system, which means that seven patients was rated as excellent, and one patient was rated as poor. Aesthetic outcomes were excellent in three patients, good in three patients, and fair in two patients. Conclusion: Our device was easy to prepare, successfully maintained the precise position of the residual mandible, and facilitated bone graft cutting and insetting during reconstruction. © 2016 Wiley Periodicals, Inc. Microsurgery 37:509–515, 2017.